9.63% efficient flexible Cu2ZnSn(S, Se)4 solar cells fabricated via scalable doctor-blading under ambient conditions. Issue 44 (3rd November 2021) - Xu, Han; Ge, Sijie; Yang, Wentao; Khan, Saqib Nawaz; Huang, Yuxiang; Mai, Yaohua; Gu, Ening; Lin, Xianzhong; Yang, Guowei
Abstract : An alternative printing via blading molecular inks with/without Na by turns in air is developed to solve the issues of Na shortage and cracks in the absorbers on Mo foil, enabling a 9.63% efficient Cu2 ZnSn(S, Se)4 flexible solar cell. Abstract : The application of doctor-blading for flexible solar cells is considerably attractive due to its potential upscaling feasibility via a roll-to-roll process. Herein, we report the fabrication of efficient flexible Cu2 ZnSn(S, Se)4 (CZTSSe) solar cells by doctor-blading under ambient conditions. The device efficiency is improved from 2.22% to 5.01% by Na incorporation, while the further enhancement is limited by inhomogeneous grain growth. To address this issue, we develop an alternative blading strategy via coating Na-containing and Na-free molecular inks by turns. By carefully tailoring this combination, compact and homogeneous CZTSSe films with large grains are obtained. Meanwhile, an appropriate amount of Na incorporation is found to be beneficial for grain growth, carrier transport, and defect passivation. Consequently, a flexible device with an efficiency of 9.63% based on the doctor-blading method is achieved. This work paves the way for the future upscaling of flexible CZTSSe solar cells via low-cost solution methods.